Political Instability, Institutions and Mortgage Credit in Lima, Peru - Zegarra, Luis F. (América Latina en la Historia Económica, 2018)
This article analyzes the evolution of the mortgage credit market in Lima between 1835 and 1865. In particular, it explores the effects of political instability and institutional change on the allocation of mortgage credit. By relying on a sample of more than 1 400 notarized records, the article suggests that political instability and institutional uncertainties led to the stagnation of credit markets in the 1830s and early 1840s. As Peru became more stable after 1845 and the risk of lending declined, the credit market expanded more rapidly and interest rates declined.